Investigation of the effectiveness of microencapsulated phase change materials for bitumen rheology - Cakti, Kaan; Erden, Ibrahim; Gunduz, Serhat; Hassanpour-Kasanagh, Sajjad; Buyuk, Baris; Alkan, Cemil (WILEY, 2022)
The rheological properties of asphalt pavement have temperature susceptibility. Bitumen is binding material and affects directly the properties of the asphalt mixture. Asphalt pavements become hard and brittle as bitumen is more sensitive to cracking in cold regions. Phase change materials (PCMs) can be used to prevent or delay freezing asphalt pavements at low temperatures. For that reason, raw n-tetradecane possessing a melting point of around 6 degrees C was preferred as an organic PCM in this study and bitumen 10/20 and 50/70 were modified with n-tetradecane. It was observed that PCM extremely rose the penetration grade of bitumen and decreased softening point due to the leakage of PCM. Three new microencapsulated phase change materials (MPCMs) were synthesized with different shell materials through emulsion polymerization technique to prevent the leakage of the PCM. Poly(methyl methacrylate) (PMMA) based MPCMs (MPCM-1 and MPCM-2) and polystyrene (PS) based MPCM (MPCM-3) were prepared with a crosslinker monomer, ethylene glycol dimethacrylate (EGDM). In addition, 2-hydroxyethyl acrylate (2-HEA) and 2-hydroxyethyl methacrylate (2-HEMA), were used as comonomer in the fabrication of MPCM-1 and MPCM-2, respectively. The latent heat storage capacities of MPCM-1, MPCM-2, and MPCM-3 were calculated as 53.3, 52.2, and 116.9 J/g, respectively. The results of the differential scanning calorimeter (DSC) analyses revealed that PS based MPCM had higher latent heat than PMMA based MPCMs. Scanning electron microscope (SEM) and particle size distribution (PSD) analyses indicated that the MPCMs had nearly spherical geometry and particles distributed around the mean particle size unimodally. Thermogravimetric analysis (TGA) exhibited that MPCMs degraded at considerably high temperatures as compared to the possible ambient ensuring high thermal durability. The current study also aims at evaluating the rheological properties of bitumen modified with PCMs and MPCMs. For this reason, softening point and penetration grade of bitumen modified with PCM and MPCM were studied. Softening point and penetration grade analyses showed that microcapsules considerably prevent leakage of PCM. Dynamic Shear Rheometer (DSR) analyses were also investigated to evaluate physical properties of bitumen modified with PCM and MPCM. DSR analyses revealed that the addition of MPCMs into bitumen preserved elastic structure and prevented softening of the bitumen as compared to the addition of PCM.
Keywords: bitumen rheology; microencapsulation; phase change materials; thermal energy; CHANGE-MATERIALS PCMS; ENERGY-STORAGE; THERMAL PERFORMANCE; ASPHALT MIXTURE; TETRADECANE; OIL; Energy & Fuels; Nuclear Science & Technology